Developing a Monte Carlo model for MEVION S250i with HYPERSCAN and Adaptive Aperture™ pencil beam scanning proton therapy system. Issue 3 (15th September 2021) - Chiang, Bing-Hao; Bunker, Austin; Jin, Hosang; Ahmad, Salahuddin; Chen, Yong
Abstract: Aim: As the number of proton therapy facilities has steadily increased, the need for the tool to provide precise dose simulation for complicated clinical and research scenarios also increase. In this study, the treatment head of Mevion HYPERSCAN pencil beam scanning (PBS) proton therapy system including energy modulation system (EMS) and Adaptive Aperture™ (AA) was modelled using TOPAS (TOolkit for PArticle Simulation) Monte Carlo (MC) code and was validated during commissioning process. Materials and methods: The proton beam characteristics including integral depth doses (IDDs) of pristine Bragg peak and in-air beam spot sizes were simulated and compared with measured beam data. The lateral profiles, with and without AA, were also verified against calculation from treatment planning system (TPS). Results: All beam characteristics for IDDs and in-air spot size agreed well within 1 mm and 10% separately. The full width at half maximum and penumbra of lateral dose profile also agree well within 2 mm. Finding: The TOPAS MC simulation of the MEVION HYPERSCAN PBS proton therapy system has been modelled and validated; it could be a viable tool for research and verification of the proton treatment in the future.